2020
DOI: 10.5847/wjem.j.1920-8642.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A pulmonary source of infection in patients with sepsis-associated acute kidney injury leads to a worse outcome and poor recovery of kidney function

Abstract: BACKGROUND: Hospital mortality rates are higher among patients with sepsis-associated acute kidney injury (SA-AKI) than among patients with sepsis. However, the pathogenesis underlying SA-AKI remains unclear. We hypothesized that the source of infection affects development of SA-AKI. We aim to explore the relationship between the anatomical source of infection and outcome in patients with SA-AKI. METHODS: Between January 2013 and January 2018, 113 patients with SA-AKI admitted to our Emergency Center were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
13
2
1
Order By: Relevance
“…ALI can easily occur in the early stage of sepsis due to the involvement of the lungs in suppurative inflammation [9]. And there are many potential pathogens that can cause sepsis [10]. More importantly, there is no drug or treatment that can effectively cure sepsis [11].…”
Section: Introductionmentioning
confidence: 99%
“…ALI can easily occur in the early stage of sepsis due to the involvement of the lungs in suppurative inflammation [9]. And there are many potential pathogens that can cause sepsis [10]. More importantly, there is no drug or treatment that can effectively cure sepsis [11].…”
Section: Introductionmentioning
confidence: 99%
“…The innate immunity and acquired immunity of the body can regulate the immune imbalance. Neutrophils, monocytes, macrophages and pathogens arrive at the site of an inflammatory reaction in large numbers, leading to tissue and vascular endothelial damage, and progress to organ failure, coagulation dysfunction and blood flow instability [9,10]. It can act on bacteria directly by secreting antimicrobial peptide, and indirectly mediate by increasing phagocytic activity of macrophages and neutrophils.…”
Section: Sepsismentioning
confidence: 99%
“…However, effective treatment is still lacking despite conventional management strategies, such as the limitation of tidal volume, maintenance of adequate high positive end-expiratory pressure (PEEP), advanced infection management, and supportive therapies. [3,4] Our previous study [5] indicated that corticosteroids could decrease the risk of ARDS in community-acquired pneumonia patients. Corticosteroids have also been reported to reduce the 28-day mortality rate in septic patients.…”
Section: Introductionmentioning
confidence: 99%